Pregnancy-related factors induce immune tolerance through regulation of sCD83 release - Krupa, Pauline; Wein, Hannah; Zemmrich, Lea Sophie; Zygmunt, Marek; Muzzio, Damián Oscar (Frontiers in Immunology, 2024)
A well-balanced maternal immune system is crucial to maintain fetal tolerance in case of infections during pregnancy. Immune adaptations include an increased secretion of soluble mediators to protect the semi-allogeneic fetus from excessive pro-inflammatory response. B lymphocytes acquire a higher capacity to express CD83 and secrete soluble CD83 (sCD83) upon exposure to bacteria-derived components such as LPS. CD83 possesses immune modulatory functions and shows a promising therapeutic potential against inflammatory conditions. The administration of sCD83 to pregnant mice reduces LPS-induced abortion rates. The increased CD83 expression by endometrial B cells as compared to peripheral blood B cells suggests its modulatory role in the fetal tolerance, especially in the context of infection. We postulate that in pregnancy, CD83 expression and release is controlled by pregnancy-related hormones. The intra- and extracellular expression of CD83 in leukocytes from peripheral blood or decidua basalis and parietalis at term were analyzed by flow cytometry. After treatment with pregnancy-related hormones and LPS, ELISA and qPCR were performed to study sCD83 release and CD83 gene expression, respectively. Cleavage prediction analysis was used to find potential proteases targeting CD83. Expression of selected proteases was analyzed by ELISA. Higher levels of CD83 were found in CD11c+ dendritic cells, CD3+ T cells and CD19+ B cells from decidua basalis and decidua parietalis after LPS-stimulation in vitro. An increase of intracellular expression of CD83 was also detected in CD19+ B cells from both compartments. Stimulated B cells displayed significantly higher percentages of CD83+ cells than dendritic cells and T cells from decidua basalis and peripheral blood. Treatment of B lymphocytes with pregnancy-related molecules (E2, P4, TGF-β1 and hCG) enhanced the LPS-mediated increase of CD83 expression, while dexamethasone led to a reduction. Similarly, the release of sCD83 was increased under TGF-β1 treatment but decreased upon dexamethasone stimulation. Finally, we found that the hormonal regulation of CD83 expression is likely a result from a balance between gene transcription from CD83 and the modulation of the metalloproteinase MMP-7. Thus, data supports and complements our previous murine studies on hormonal regulation of CD83 expression, reinforcing its immunomodulatory relevance in anti-bacterial responses during pregnancy.